Parent-Teacher Engagement and Academic Performance of Grade One Pupils in Public Elementary Schools - Aparato, Mary Joy (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the extent of parent-teacher engagement and the academic performance of Grade One pupils in selected public elementary schools in the Binangonan District, Schools Division Office of Rizal, during the School Year 2025–2026. Specifically, it assessed parent-teacher engagement in terms of parenting, communicating, volunteering, and collaborating, examined the academic performance of pupils, and determined the significant differences and relationships among the study variables. The study employed a descriptive survey research design complemented by documentary analysis. Respondents consisted of 57 Grade One teachers and 325 parents selected through Slovin’s formula and simple random sampling. Data were gathered using a validated researcher-made questionnaire, while pupils’ average grades were obtained through documentary analysis to measure academic performance. Descriptive and inferential statistical tools were utilized in analyzing the data. Findings revealed that both teachers and parents perceived parent-teacher engagement to a high extent. Significant differences existed between the perceptions of teachers and parents regarding parenting and communicating, while no significant differences were found in volunteering and collaborating. Teachers’ demographic characteristics did not significantly influence their perceptions of parent-teacher engagement. Similarly, parents’ perceptions did not significantly differ based on age, sex, civil status, number of children, and monthly family income; however, educational attainment and occupation showed significant differences. Grade One pupils attained a very satisfactory level of academic performance. Correlation analysis indicated that only the parenting dimension of parent-teacher engagement had a significant relationship with pupils’ academic performance, whereas communicating, volunteering, and collaborating were not significantly associated with academic achievement. The study concluded that effective parenting practices remain the most influential dimension of parent-teacher engagement in supporting pupils’ academic success. It recommends that school administrators strengthen parent education programs, improve communication systems, expand opportunities for meaningful parent participation, and implement the proposed action plan. Teachers are likewise encouraged to sustain collaborative partnerships with parents that recognize both learners’ needs and achievements. Future studies may explore additional variables that may influence parent-teacher engagement and pupils’ academic performance.